The Rockets and Feathers of Inflation Attention - Oleg Korenok; David Munro (Global Labor Organization (GLO), 2024)
Prior research has documented that attention to inflation shifts when inflation surpasses a 3-4% threshold. In this note we examine how attention to inflation declines in episodes of disinflation. We show that for countries where inflation has returned to "normal" (pre-threshold) levels, attention remains 2-3 times higher than it was before the run-up of inflation. We show evidence that wage growth is more strongly correlated with past inflation when attention is high. This is one possible mechanism behind the slower-than-expected disinflation in late 2023 and early 2024.
Keywords: E31; E52; E70; 330; inflation; attention; persistence; threshold